Assessing the impact on growth and yield in different varieties of chili pepper (Capsicum frutescens) intercropped with chaya (Cnidoscolus aconitifolius) - FITRA GUSTIAR; BENYAMIN LAKITAN; DEDIK BUDIANTA; ZAIDAN P. NEGARA (Society for Indonesian Biodiversity, 2023)
Abstract. Gustiar F, Lakitan B, Budianta D, Negara ZP. 2023. Assessing the impact on growth and yield in different varieties of chili pepper (Capsicum frutescens) intercropped with chaya (Cnidoscolus aconitifolius). Biodiversitas 24: 2639-2646. Intercropping chaya and chili plants is advantageous as it can boost land productivity and increase farmer income. However, the growth of the chili plant is more likely to be hampered by the shade formed by the canopy of the chaya plant. Therefore, this study aimed to investigate the response of chili to the shade of the chaya plant canopy and identify varieties that can thrive in intercropping systems. The experiment was arranged based on a split-plot design with a planting pattern as the main plot, consisting of chili monoculture, intercropping of chaya-chili, and intercropping of pruned-canopy chaya with chili. Three chili varieties, i.e., Rajo, Taruna, and Bara, were the subplots with four replications. Chaya plants were planted at a distance of 200 x 200 cm. Chaya-chili intercropping was done by inserting two rows of chili plants with a distance of 50 x 50 cm between rows of chaya plants. The results showed that chili pepper planted in an intercropping system exhibit an etiolation effect as indicated by a taller stem but with fewer leaves than the chili plants cultivated with a monoculture system. The shading effect of the chaya plant resulted in lower leaf temperature of the chili peppers in intercropping system. Pruning treatment on the shoots of chaya plants positively impacted the growth and yield of chili plants, which was indicated by an increase in biomass weight and fruit yield. The Bara variety was harvested two weeks earlier and produced higher fruit yields compared to Rajo and Taruna varieties. The growth and yield of chili plants were relatively comparable between the monoculture and intercropping system if the canopy pruning in chaya plants was carried out, especially in the Bara variety.